2021
DOI: 10.1111/jnc.15357
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine improves aging‐induced cognitive impairment and brain regional neurodegeneration in relation to the neuropathological alterations in the secondary structure of amyloid beta (Aβ)

Abstract: Aging‐induced proteinopathies, including deterioration of amyloid beta (Aβ) conformation, are associated with reductions in endogenous levels of carnosine and cognitive impairments. Carnosine is a well‐known endogenous antioxidant, which counteracts aging‐induced Aβ plaque formation. The aim of this study was to investigate the effects of exogenous carnosine treatments on aging‐induced changes (a) in the steady‐state level of endogenous carnosine and conformation of Aβ secondary structure in the different brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Therefore, this group thought of supplementing aged Wistar rats with carnosine in order to check if it could alleviate age-related phenotypes. The results obtained in this study indicated that carnosine was able to attenuate aging-induced Aβ plaque formation and improve cognitive impairment in elderly rats [101]. In addition, galactose treatment has been stablished as a model of accelerated aging in rats since it leads to an increase in OS levels.…”
Section: Aging-related Neurodegenerationmentioning
confidence: 63%
“…Therefore, this group thought of supplementing aged Wistar rats with carnosine in order to check if it could alleviate age-related phenotypes. The results obtained in this study indicated that carnosine was able to attenuate aging-induced Aβ plaque formation and improve cognitive impairment in elderly rats [101]. In addition, galactose treatment has been stablished as a model of accelerated aging in rats since it leads to an increase in OS levels.…”
Section: Aging-related Neurodegenerationmentioning
confidence: 63%
“…In addition, there is a growing number of consumers using the dipeptide because of its supposed general anti-aging capabilities based on its effects on ROS [ 7 ], which also attracted interest in using it as a component of cosmetic products [ 8 , 9 ]. Protecting against glycating sugars [ 10 ], methylglyoxal [ 11 ], advanced glycation end-products [ 12 ], and amyloid-β peptides [ 13 ], carnosine has also been considered as a therapeutic drug for the treatment of Alzheimer’s disease or cognitive decline in general [ 14 ] and Parkinson’s disease [ 15 ]. Based on experiments performed with cell culture and animal models, carnosine has also been considered as a drug for the treatment of different forms of cancer [ 16 , 17 , 18 , 19 , 20 ] including glioblastoma which is a highly malignant form of brain tumor (for review see [ 21 , 22 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Carnosine is a bioactive molecule that has been indicated to provide protective benefits for counteracting to neurodegenerative conditions [ 30 ]. Recent studies reported that carnosine can inhibit the aggregation of amyloidogenic proteins such as α-crystallin and Aβ42 [ 21 , 31 , 32 ], which may ameliorate the toxicity of protein aggregates.…”
Section: Resultsmentioning
confidence: 99%